Cover Image. (7th February 2023) - Shen, Xiaoting; Yang, Sijia; Xu, Yangbo; Qi, Wenting; He, Fuming
Abstract : The cover image is based on the Original Article Marginal bone loss of tissue‐ or bone‐level implants after simultaneous guided bone regeneration in the posterior mandibular region: A retrospective cohort study by Xiaoting Shen DDS et al., https://doi.org/10.1111/cid.13144 . Abstract : The cover image is based on the Original Article Marginal bone loss of tissue‐ or bone‐level implants after simultaneous guided bone regeneration in the posterior mandibular region: A retrospective cohort study by Xiaoting Shen DDS et al., https://doi.org/10.1111/cid.13144 .